Predictors of Malreduction in Zone II and III Fifth Metatarsal Fractures Fixed With an Intramedullary Screw. (December 2020) - Khurana, Ankit; Alexander, Bradley; Pitts, Charles; Brahmbhatt, Ashish; Cage, Benjamin; Greco, Elise; McGwin, Gerald; Shah, Ashish B.
Background: Proper implant selection and placement is crucial during fixation of zone II and III fifth metatarsal fractures to avoid postoperative complications. This study examined the effects of screw parameters and placement on malreduction, delayed union, nonunion, and refracture rate. Methods: A retrospective review of zone II and proximal zone III fifth metatarsal fractures managed with intramedullary screw fixation was conducted. Comparisons were made between cortex distraction (gap) and ratios of screw length, diameter, and entry point. Further analysis was carried out between time to union and distraction in the lateral and plantar cortices. Results: The plantar and lateral gaps were both associated with the mean entry point ratio on the lateral and anteroposterior (AP) views ( P < .001 for both views). No association between the plantar and lateral gaps and the screw diameter ratio ( P = .393 for AP and P = .981 for lateral) or the screw length ratio ( P = .966 for AP and P = .740 for lateral) was identified. The ratio of postoperative to preoperative apex height on AP and lateral views was correlated with the presence of lateral and plantar fracture gaps ( P < .001). The presence of a plantar gap was associated with increased time to union ( P = .022). A majority of fractures showed radiographic union at 12 weeks (38/43). Only 5 of 38 patients had delayed union. There were no refractures or nonunions as per available records. Conclusion: Plantar or lateral fracture site distraction (gap) was not influenced by screw diameter ratio or screw length ratio. The entry point ratio had a significant effect on plantar and lateral gaps on postoperative radiographs, with lateral and inferior placement leading to fracture site distraction. Patients with a plantar gap did have an increased risk of delayed union. The results of this study emphasize the significance of the entry point when managing zone II and III fifth metatarsal base fractures. Level of Evidence: Level IV, case series.